(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2001)
The purpose of the study is to identify and classify occurrences of Ellipsis in question-answer and other rejoinder sequences in one type of communicative interaction, that is, the interview, in order to: (a) Describe its contribution to oral sexual coherence and interaction progression and, (b) establish variation originating in the age and sex of participants. The purpose was taken from interviews with six upper-social-stratum men and women from Valdivia divided into three groups. The results share the significant presence of ellipsis in communicative interaction, as well as its contribution to the progression of the interaction and to the coherence of the oral texts examined. The analysis shows that variations is not only conditioned by speakers’ decisions with respect to what they say, but also by their attitude towards the interviewers’ observations( questions and other utterances). The interviewees’ attitude changed significantly between men and women, and between the oldest generation and the two younger generations